Comparison of Platelet Levels between Preeclampsia and Eclampsia Patients at Wiyung Sejahtera Hospital, Surabaya - Fortuna Maudy Sintya, Reyke; Dwi Ariningtyas, Ninuk; Nurida, Annisa; Salim Ambar, Nabil (Universitas Muhammadiyah Semarang, 2021)
Background: Indonesia is a developing country with a high maternal mortality rate (MMR) and perinatal mortality, the third highest in ASEAN and the second highest in the South East Asian Nation Regional Organization. In pregnancy hypertension has been proven that oxidants, especially if increased fat peroxide will damage endothelial cells called endothelial dysfunction. Vasospasm that occurs also induces platelet integration and endothelial damage which adds to the contribution in maintaining platelet dysfunction and triggering the use of platelets. Thrombocytopenia is the most important sign of the severity of preeclampsia.Objective: to determine the comparison of platelet levels in patients with preeclampsia with eclampsia.Methode: This study was observational cross sectional method. The sample in this study was a total sampling, using purposive sampling of patients with preeclampsia and eclampsia at the Wiyung Sejahtera Hospital in January-December 2019. The instrument used was using secondary data of medical records of patients.Results: Patients with preeclampsia have a minimum platelet level of 301,000/mm3, a maximum of 415,000/mm3, and an average of 351,733.33/mm3 with a standard deviation of 33,552.66/mm3. Patients with eclampsia have a minimum platelet level of 122,000/mm3, a maximum of 281,000/mm3, and an average of 209,200/mm3 with a standard deviation of 42,465.45/mm3. There are significant differences in platelet levels of patients with preeclampsia with eclampsia(p <0.05)..Conclusion: there is a significant difference between the platelet levels of patients with preeclampsia and eclampsia.